PROFESSIONAL IDENTITY QUESTIONNAIRE FOR PSYCHOLOGICAL HELP PROVIDERS: DEVELOPMENT AND VALIDATION - Akmane, Elīna; Mārtinsone, Kristīne; Krieķe, Zane; Perepjolkina, Viktorija; Drunka, Agnese; Kolmane, Agnese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of this research was to develop multiscale questionnaire of professional identity (PI) and to test its psychometric properties. This research was conducted in 3 phases. During the first phase a scoping review, a focus group discussion, and a rapid literature review were conducted to identify the criteria of PI. Survey items were constructed and assessed in the second phase. The data were collected, and the psychometric properties were examined in the third phase. The survey was completed by 239 psychological help providers in Latvia (psychiatrists (n = 13), nurses (n = 37), psychotherapists (n = 8), art therapists (n = 45), psychologists (n = 55), psychotherapy specialists (n = 28) and social workers (n = 53)) aged between 22 and 80 years (M = 45.8; SD = 10.6) of which 95% women (n = 227) and 5% men (n = 12). As a result, 8 factors structure was confirmed (k = 38). Overall, it can be concluded that the survey examines a unified phenomenon, and the items are internally consistent on all scales (α = .715 - .873). The development of this questionnaire is an important step towards the research of PI.